Hubungan Peran Perawat sebagai Edukator dengan Kepatuhan Mobilisasi Pasien Infark Miokard Akut - Anis Nurani (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2016)
The mobilization obedience of patients with IMA was an intention and patient ability to mobilize early, continue, step by step, individual depend on their condition, to get optimal of physical function, mental and social. This behavior emerged because there was an interaction between health employees and patient, so patient will know the plan, consistence and agree for that. This research was aimed to know relation of nursing role as educator with obedience of mobile to patient's IMA. Design used in this study was cross sectional. The data analyzed with Chi Square's analyze. The population was all of patients with IMA. The sample was 14 respondents, taken by total sampling. This research was done in Wijaya Kusuma's room, Ngudi Waluyo Hospital at November 2014. The independent variable was nursing role as educator and dependent variable was mobilization obedience of patients with IMA. The data collection used questionnaire. Result of this research showed that there was correlation of nursing role as educator and mobilization obedience of patients with IMA with value of  2 = 4,381 and significance level = 0,036. Conclusion of this research was good nursing role as educator would determine a better mobilization obedience of patients with IMA.